Fungal iron availability during deep seated candidiasis is defined by a complex interplay involving systemic and local events. - Joanna Potrykus (Public Library of Science (PLoS), 2013)
Nutritional immunity--the withholding of nutrients by the host--has long been recognised as an important factor that shapes bacterial-host interactions. However, the dynamics of nutrient availability within local host niches during fungal infection are poorly defined. We have combined laser ablation-inductively coupled plasma mass spectrometry (LA-ICP MS), MALDI imaging and immunohistochemistry with microtranscriptomics to examine iron homeostasis in the host and pathogen in the murine model of systemic candidiasis. Dramatic changes in the renal iron landscape occur during disease progression. The infection perturbs global iron homeostasis in the host leading to iron accumulation in the renal medulla. Paradoxically, this is accompanied by nutritional immunity in the renal cortex as iron exclusion zones emerge locally around fungal lesions. These exclusion zones correlate with immune infiltrates and haem oxygenase 1-expressing host cells. This local nutritional immunity decreases iron availability, leading to a switch in iron acquisition mechanisms within mature fungal lesions, as revealed by laser capture microdissection and qRT-PCR analyses. Therefore, a complex interplay of systemic and local events influences iron homeostasis and pathogen-host dynamics during disease progression.